Bifidobacterium animalis ssp. lactis BI07 modulates the tumor necrosis factor alpha-dependent imbalances of the enterocyte-associated intestinal microbiota fraction. Issue 2 (1st August 2014) - Centanni, Manuela; Turroni, Silvia; Rampelli, Simone; Biagi, Elena; Quercia, Sara; Consolandi, Clarissa; Severgnini, Marco; Brigidi, Patrizia; Candela, Marco
Abstract: Using a previously developed in vitro model to characterize the enterocyte-adherent microbiota fraction, we explored the potential of the probiotic strain Bifidobacterium animalis ssp. lactis BI07 to modulate the inflammation-dependent dysbioses of the enterocyte-adherent microbiota from 12 healthy human donors. According to our findings, B. animalis ssp. lactis BI07 is effective in limiting the increase of pro-inflammatory pathobionts on the inflamed mucosal site, supporting the recovery of a mutualistic community. Abstract : Bifidobacterium animalis subsp. lactis BI7, a well-known probiotic strain, has shown the potential to redress inflammation-dependent dysbioses of the enterocyte adherent fraction of the human intestinal microbiota. Abstract :